Staphylinidae Latreille, 1803- 1802 - Majka, Christopher G.; Klimaszewski, Jan; Lauff, Randolph F. (Zenodo, 2006)
Staphylinidae Phyllodrepa floralis (Paykull) is an adventive Palearctic species found throughout Europe, north to Iceland, east to Russia, south to the Caucasus, and west through Turkey to Algeria in North Africa (Herman 2001). It is found throughout Canada from British Columbia to Newfoundland (Campbell & Davies 1991). It has previously been associated with bird and mammal nests (Steel 1970, Newton et al. 2001). In this study P. floralis was recorded only in a boreal owl nest. Hylota ochracea Casey: the genus Hylota Casey 1906 has been regarded as a synonym of Oxypoda Mannerheim 1830 (Seevers 1978) but will be reelevated to its generic status by Klimaszewski et al. (submitted). It is known from New York, Ontario, Québec, Northwest Territories (Klimaszewski et al. submitted), and Nova Scotia (C.G. Majka, unpublished data). Nothing has previously been reported about the natural history of this species, so these records, from both boreal and northern sawwhet owl nests, represent the first information about its bionomics. Published as part of Majka, Christopher G., Klimaszewski, Jan & Lauff, Randolph F., 2006, New Coleoptera records from owl nests in Nova Scotia, Canada, pp. 33-47 in Zootaxa 1194 on page 37, DOI: 10.5281/zenodo.2646209